2018
DOI: 10.29271/jcpsp.2018.07.549
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Burnout, Self-esteem And Professional Life Quality Of Nurses

Abstract: In this study, it was detected that burnout in nurses affected compassion satisfaction and individual success negatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
2
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 0 publications
1
29
2
5
Order By: Relevance
“…From our study, high mean self-esteem scores are illustrated by the majority of nurses 68.0% as compared to 0.6% and 31.4% who scored low and normal self-esteem, respectively. Regarding self-esteem, our study results contradict those reported by Erkorkmaz et al [31], who reported a lower mean among Turkish nurses. The difference could be thought of due to different healthcare and employment policies that vary among countries.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…From our study, high mean self-esteem scores are illustrated by the majority of nurses 68.0% as compared to 0.6% and 31.4% who scored low and normal self-esteem, respectively. Regarding self-esteem, our study results contradict those reported by Erkorkmaz et al [31], who reported a lower mean among Turkish nurses. The difference could be thought of due to different healthcare and employment policies that vary among countries.…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding the relationship between self-esteem and burnout, our study revealed negative relationship with emotional exhaustion (Unstandardized coefficient: -0.212, p-Value = 0.001) and depersonalization (Unstandardized coefficient: -0.212, p-Value = 0.001); and positive relationship with personal achievement (unstandardized coefficient: 0.068, p-Value = 0.554). Supporting our study's results by proportions of burnout subscales, Erkorkmaz et al [31] also reported a negative relationship between burnout versus self-esteem. This is due to the loss of morale for work related to loss of self-worth [36].…”
Section: Plos Onesupporting
confidence: 90%
“…Furthermore, researchers have indicated that fatigue can have a negative impact on health and contribute to decision regrets, that is negative emotions in response to unexpected outcomes of the nurse's decisions (Scott, Arslanian‐Engoren, & Engoren, ), absenteeism (K. Sagherian, G. J. Unick et al, ), dissatisfaction (Steege & Rainbow, ), burnout, and lower well‐being among nurses (Stimpfel, Sloane, & Aiken, ). In turn, burnout and dissatisfaction with work could negatively affect nurses’ quality of life as well as the quality of the nursing care provided to patients (Erkorkmaz, Dogu, & Cinar, ; Ibrahim et al, ; Naz, Hashmi, & Asif, ).…”
Section: Introductionmentioning
confidence: 99%
“…간호현장에서의 스트레스 관리는 임상간호사들의 직장생활 만족도를 증가시켜 직장과 개인생활의 균형을 통하여 간호사의 직무 소진을 감소시킨 다 (Choi JL, 2014). 이러한 간호사의 직무와 관련된 스트레 스와 정신건강에는 자아존중감이 유의한 상관관계가 있는 것으로 여러 선행연구에서 밝혀진 바 있다 (Lee HS, 2013; Jun YJ et al, 2014;Erkorkmaz et al, 2018). 자아존중감은 소진에 영향을 주는 요인으로 자신을 하나 의 특별한 개체로 이해하며, 자신에 대한 부정적 혹은 긍정 적인 태도를 보이는 것과 스스로가 얼마나 가치있는 존재인 가를 느끼는 정도로서 (Rosenberg M, 1965), 내적으로 변화 할 수 있는 힘을 부여하는 개인의 내적자원이다 (Kim MJ et al, 2015).…”
unclassified